Spinal Syphilitic Gumma: A Rare Presentation of an Old Disease - Dominic Worku; Angela Houston; Catherine Cosgrove; Laura Byrne (Case Reports in Infectious Diseases)
Syphilis is an ancient condition which still is of global concern today. Despite better awareness amongst clinicians and improving diagnostics, it remains likely underdiagnosed in part because of its namesake the ‘great imitator.’ While many patients suffer primary or secondary disease, tertiary syphilis characterised by gumma is rare, especially in the context of neurosyphilis. Here, we report a rare case of a well-controlled human immunodeficiency virus- (HIV-) positive gentleman with a history of previous syphilis and epilepsy who presented with progressive left leg weakness leading to immobility and altered bowels and, on neurological examination, Brown-Sequard syndrome. Magnetic resonance imaging (MRI) of the spine revealed two peripherally enhancing cavitating lesions at T4-T5 with associated meningeal thickening and cord oedema. Cerebrospinal fluid (CSF) analysis revealed high protein (3.07 g/dL) and white cell count (7 × 109/L) with negative cryptococcal antigen, tuberculosis molecular testing (GeneXpert), microscopy and culture, and viral polymerase chain reaction (PCR). CSF serology was positive for Treponema pallidum particle agglutination (TPPA) 10240 and RPR 1 in 2 suggesting active disease. While TB treatment had been started prior to these investigations on day 11, 14-day high-dose benzylpenicillin therapy commenced. Repeat MRI of the spine at days 12 and 22 showed incremental improvements in all parameters which correlated with improving functionality and neurology. According to our literature search, this represents the 13th case recorded for spinal syphilitic gumma and the only case recorded in a HIV-positive individual and adds to the evidence that, in the absence of rapidly changing neurology, medical management can lead to good clinical outcomes.